THE INTERSECTION OF CORPORATE GOVERNANCE, ETHICS, INTERNAL AUDIT, AND BANKRUPTCY RISK MANAGEMENT: A BIBLIOMETRIC ANALYSIS - Carmen Mihaela Bulău; Mirela Matei (Pană); Aura Oana Mustățea; Mihaela Denisa Coman (Agora International Journal of Economical Sciences)
This study employs a mixed-methods approach to delve into the intricate interplay among corporate governance, bankruptcy risk, forensic accounting, internal auditing, and ethics. While prior research has highlighted the correlation between weak governance, increased bankruptcy risk, and ethical lapses, the synergies among these factors necessitate deeper investigation. The authors conducted a meticulous bibliometric analysis of the Scopus database, focusing on the realms of accounting, internal audit, forensics, bankruptcy, and ethics within the overarching domain of corporate governance. Emphasizing the importance of robust governance principles in mitigating risks in accounting, the study revealed a substantial coverage of resources across various disciplines, with accounting (54.6%) and ethics (25.1%) leading the distribution. The dataset, comprising 5990 resources from 495 publications cited 151,911 times spanning from 1978 to March 2024, serves as a valuable resource for scholars aiming to fortify organizational resilience by integrating critical concepts identified in this research.